Implementation of Regional Government Information Systems in the Administration Process - Bahri, Samsul; Ohorela, Zulkifli; Salim, Saiful; Samsuddin, Risky P.; Fergiawan, Fergiawan (Borong Newinera Publisher, 2025)
This study examines the implementation of a local government information system in the financial administration processes at the Regional Financial and Asset Management Agency (BPKAD) in Tidore Islands City. This information system is expected to enhance efficiency, transparency, and accountability in regional financial administration. Using a qualitative approach, the study explores BPKAD employees' experiences and perceptions regarding system effectiveness, implementation challenges, and its alignment with local policies and needs. The findings indicate that while the information system contributes to more effective financial management, challenges persist in infrastructure, human resources, and policy support. The study provides recommendations for system improvements, staff training, and policy adjustments to enhance financial management effectiveness at the local government level.